Clinical characteristics and clinical outcome of community clusters with SARS-CoV-2 infection - Zhu, Xueling; Wu, Wenrui; Ning, Jianwen; Dai, Tingting; Fang, Daiqiong; Wu, Jingjing; Shi, Ding (Frontiers in Public Health, 2023)
Background Community clustering is one of the main features of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). However, few studies have been conducted on the clinical characteristics and clinical outcome of clustered cases and sporadic cases with COVID-19. Methods We recruited 41 community clusters confirmed with SARS-CoV-2 infection compared with 49 sporadic cases in Zhejiang Province from 19 January 2020 to 9 June 2020. Clinical data were collected to evaluate the clinical outcome and characteristics of community clusters. Results Compared to sporadic cases, clustered cases had significantly lower Acute Physiology and Chronic Health Evaluation II (APACHE II) score {5.0 [interquartile range (IQR), 2.0–7.5] vs. 7.0 [IQR, 4.0–12.5]; P = 0.005}, less members in intensive care unit (ICU) (6 [14.6%] vs. 18 [36.7%]; P = 0.018), and shorter time of viral shedding in fecal samples (18.5 [IQR, 17.0–28.3] vs. 32.0 [IQR, 24.3–35.5]; P = 0.002). Univariable logistic regression revealed that older age (odds ratios 1.078, 95% confidence intervals 1.007–1.154, per year increase; p = 0.032), high APACHE II score (3.171, 1.147–8.76; P = 0.026), elevated interleukin-2 levels (3.078, 1.145–8.279; P = 0.026) were associated with ICU admission of clustered cases. Conclusions Compared to sporadic cases, clustered cases exhibited milder disease severity and a better clinical outcome, which may be closely related to the management of early detection, early diagnosis, early treatment and early isolation of COVID-19.